"Opening the door": developing and pilot testing an adult protective services worker engagement training in New York city. Issue 3 (27th May 2019) - Halarewicz, A.K.; Gelman, Caroline; Ghesquiere, Angela; Rogers, Geoffrey
ABSTRACT: About 10% of Americans over the age of 60 experience elder abuse (EA), but EA is frequently under detected. As the primary responders for alleged EA cases, Adult Protective Service (APS) caseworkers are ideally positioned to improve detection and intervention. The Opening the Door (OTD) training was developed in a multidisciplinary setting and designed in collaboration with APS workers to enhance their engagement skills in potential EA cases and thus maximize the possibility of disclosure. Rooted in a relational approach and utilizing adult learning theory, it is divided into three main topics: Preparing for Engagement, Engagement Practice, and Processing Engagement. The eight-hour training was piloted with three groups of urban APS caseworkers with a wide range of work experience. Pre- and post-tests and case reflections indicate a positive impact on caseworkers' sense of self-efficacy, while focus groups indicate the necessity for ongoing provision of trainings and development of additional supports for APS caseworkers. Future work could further explore the efficacy of the training and expand its reach.